Temporal Analysis of the Incidence, Mortality and Disability-Adjusted Life Years of Benign Gallbladder and Biliary Diseases in High-Income Nations, 1990–2019 - Dominic W. Proctor, BMBS, MSc; Richard Goodall, BSc, MBChB, MRCS, FHEA; Kim Borsky, MBBS, MMRCS; Justin D. Salciccioli, MBBS, MA; Dominic C. Marshall, MBBS, MRCP, BSc; Kumaran Shanmugarajah, MD, PhD; Joseph Shalhoub, BSc, MBBS, FHEA, PhD, DIC, MEd, FFSTEd, FRCS, FEBVS (Annals of Surgery Open)
Objective:. The aim of this observational study was to analyze trends in the incidence, mortality, and disability-adjusted life years (DALYs) of benign gallbladder and biliary diseases across high-income countries between 1990 and 2019. Background:. Benign gallbladder and biliary diseases place a substantial burden on healthcare systems in high-income countries. Accurate characterization of the disease burden may help optimize healthcare policy and resource distribution. Materials and methods:. Age-standardized incidence rates (ASIRs), age-standardized mortality rates (ASMRs), and DALYs data for gallbladder and biliary diseases in males and females were extracted from the 2019 Global Burden of Disease (GBD) study. A mortality-incidence index (MII) was also calculated. Joinpoint regression analysis was performed. Results:. The median ASIRs across the European Union 15+ countries in 2019 were 758/100,000 for females and 282/100,000 for males. Between 1990 and 2019 the median percentage change in ASIR was +2.49% for females and +1.07% for males. The median ASMRs in 2019 were 1.22/100,000 for females and 1.49/100,000 for males with a median percentage change over the observation period of −21.93% and −23.01%, respectively. In 2019, the median DALYs was 65/100,000 for females and 37/100,000 among males, with comparable percentage decreases over the observation period of −21.27% and −19.23%, respectively. Conclusions:. International variation in lifestyle factors, diagnostic and management strategies likely account for national and sex disparities. This study highlights the importance of ongoing clinical efforts to optimize treatment pathways for gallbladder and biliary diseases, particularly in the provision of emergency surgical services and efforts to address population risk factors.